A hospital-to-home evaluation of an enhanced recovery protocol for elective pancreaticoduodenectomy in China: A cohort study. Issue 41 (October 2017) - Su, Wei; Lu, Fangyan; Zhang, Xiaoyu; Li, Guogang; Chen, Wei; Ma, Tao; Gao, Shunliang; Lou, Jianying; Bai, Xueli; Liang, Tingbo
Abstract : Abstract: Enhanced recovery after surgery (ERAS) programs have been shown to decrease postoperative complications and hospital stay in pancreaticoduodenectomy. However, no studies concerned recovery after discharge except readmission. This study evaluated an ERAS program for pancreaticoduodenectomy from hospital to home. A prospective ERAS cohort undergoing elective pancreaticoduodenectomy was compared with a retrospective control group in terms of postoperative complications and hospital stay, and home recovery after discharge. Propensity-score matching was used to balance their baselines. Two groups of 31 patients with similar propensity scores were established. Postoperative morbidities were 18 of 31 and 26 of 31 in the ERAS and control groups, respectively ( P  = .06). Patients in the ERAS group suffered from fewer cardiovascular complications (3/31 vs 11/31; P  = .04) and intestinal dysbacteriosis (4/31 vs 13/31; P  = .04). Median postoperative hospital stay was shorter in the ERAS group (8 vs 16 days; P  < .001). Although the 2 groups were similar in terms of sleep, defecation, vigor, performance status, and pain control in first month after discharge, patients in the ERAS group enjoyed better food intake recovery (18/31 vs 5/31 in first week, P  = .002; 22/31 vs 9/31 in second week, P  = .008; 23/31 vs 13/31 in fourth week, P  = .01) and fewer weight loss (10/31 vs 19/31; P  = .05). Multivariate analyses showed that both improvements were associated with no bowel preparation. ERAS implementation in selected patients undergoing pancreaticoduodenectomy could promise better outcomes, not only in the hospital but also at home in the short term. Abstract : Supplemental Digital Content is available in the text